Process simulation for recombinant human lysozyme production from transgenic rice: impact of intensification strategies. - Huseman, Zebulun K. (My University, 2026)
Traditional batch bioprocessing dominates biologics manufacturing but faces limitations in equipment utilization, high costs, and scalability, particularly for downstream purification. This report evaluates the economic and technical impacts of process intensification on the downstream production of recombinant human lysozyme (rHLZ) from transgenic rice seed. Using SuperPro Designer (Intelligen, Inc.), five distinct purification train configurations were modeled to meet a projected annual market demand of 1,000 kg/yr. This production target was established through a demographic-based analysis of children with egg-white allergies who require safe, plant-based alternatives to traditional animal-derived lysozyme. The configurations examined in this study range from traditional methods to highly integrated systems. The baseline batch model serves as the industry standard, utilizing sequential processing and significant intermediate storage. The pool-less strategy attempts to reduce capital costs by eliminating non-essential hold tanks, while the high-capacity resin model explores the use of a modern chromatography resin which reduces column size and buffer consumption and enhances binding capacity and life span of the resin. More advanced strategies include the semi-continuous model, which employs cyclic extraction and a rotary vacuum drum filter to maximize equipment utilization, and the combined intensification model, which integrates the most effective elements from all previous configurations. The results of the simulation analysis reveal a significant disparity in performance between traditional and intensified designs. The baseline batch configuration proved to be the most resource-intensive, requiring a capital expenditure of $26 million and resulting in a cost of goods of $12.2/g. In striking contrast, the combined intensification model emerged as the most efficient, reducing capital expenditure by 60% and lowering the cost of goods 40% while simultaneously improving volumetric productivity. Ultimately, this research demonstrates that the strategic implementation of semi-continuous operations and process intensification strategies using high-capacity resins can substantially lower the economic barriers to producing biologics within plant-based seed expression systems.
Keywords: Process simulation; Recombinant human lysozyme; Transgenic rice; Intensification